Treatment-resistant depression: Current therapeutic strategies - Samuel Cândido Freres; Marco Antonio Franco Cançado; Aline Ferreira Catrolio; Vanderli Barbosa Amaecing; Sharie Lohanna de Moraes Nascimento (International Health Sciences Review, 2026)
Treatment-resistant depression (TRD) represents one of the most complex forms of major depressive disorder, characterized by the persistence of clinically significant symptoms despite the performance of appropriate therapeutic interventions. This condition is associated with a worse prognosis, higher risk of recurrence, functional impairment, increased morbidity and mortality, and high socioeconomic impact. The objective of this article was to review the main aspects related to ESRD, addressing its definition, diagnostic criteria, epidemiology, pathophysiological mechanisms, and currently available therapeutic strategies. A narrative review of the literature was carried out, including national and international studies that discuss advances in the management of resistant depression. It is observed that the pathophysiology of ESRD involves alterations in mon oaminergic and glutamatergic neurotransmission, reduced neuroplasticity, inflammatory processes, neuroendocrine dysfunctions, and genetic factors, justifying the limited efficacy of conventional antidepressants in some patients. Current therapeutic strategies include optimization and combination of antidepressants, pharmacological potentiation, use of atypical antipsychotics, lithium, and thyroid hormones, as well as innovative therapies such as ketamine and esketamine, which demonstrate rapid antidepressant response in selected cases. It is concluded that the management of ESRD should be individualized, based on up-to-date scientific evidence, and integrated with multidisciplinary approaches, aiming at symptom remission, functional recovery, and improvement of patients' quality of life.